Shape effects on the electronic structure and the optical gain of InAsN/GaAs nanostructures : from a quantum lens to a quantum ring - Xu, Q. (2013)
The electronic structures of self-assembled InAs1−xNx/GaAs nanostructures from quantum lens to quantum rings (QRs) are calculated using the 10-band k.p method and the valence force field (VFF) method. With the variation of shape of the nanostructure and nitrogen (N) content, it shows that the N and the strains can significantly affect the energy levels especially the conduction band because the N resonant state has repulsion interaction with the conduction band due to the band anticrossing (BAC). The structures with N and greater height have smaller transition energy, and the structures with N have greater optical gain due to its overwhelming greater value of factor fc+fv−1fc+fv−1. After analyzing the shape effect, we suggested that the nanostructures with volcano shape are preferred because the maximum optical gain occurs for quantum volcano. With our simulation result, researchers could select quantum dots (QDs) structures to design laser with better performance.